The Basis and Motivation of Entrepreneurship in Islam - Sulistia Ningrum; Siti Wasilah; Moh. Hamzah (Penerbit Hellow Pustaka, 2025)
Entrepreneurship in the Islamic perspective is not solely profit-oriented, but also emphasizes spiritual values, ethics, and social responsibility. This research was conducted due to the urgency of building a holistic understanding of the role of Islamic entrepreneurship in shaping a just and sustainable economic system. The purpose of this study is to analyze the motivations and characteristics of entrepreneurs in Islam, as well as to examine the strategic role of entrepreneurship in the lives of Muslim individuals and communities. This study employs a qualitative method with a library research approach. Data sources are obtained from primary and secondary literature such as the Qur'an, hadith, books, and scholarly journals on Islamic economics and entrepreneurship. The results indicate that the primary motivation of a Muslim entrepreneur is not merely profit-seeking but also to attain the pleasure of Allah, improve the welfare of the ummah, and fulfill social responsibilities. The main characteristics required include honesty, trustworthiness, hard work, innovation, and a strong commitment to moral values and social benefit. This research is significant in providing a conceptual framework for the development of entrepreneurship based on Islamic values, both in education and in practical economic activity. It is expected to foster entrepreneurs who are not only financially successful but also contribute positively to society and national development.